The Hermeneutic Situation of the Teacher-Researcher: a proposal to Conduct Research in the Field of Education using Prejudice and Autoethnography - Moreno Aponte, Rodrigo (2016)
The paper uses the hermeneutic methodology in the field of Social Sciences. This methodology is characterized for being a position that departs from the traditional epistemological differentiation between the subject and the object. The experience and situational context of the researcher are linked with the subject of study. To develop these ideas, the author describes hermeneutics as developed by Hans-Georg Gadamer, focused on the concept of prejudice. In the paper, these ideas are related to the researchtechnique known as autoethnography. Finally, emphasis is given to the ties betweenthese two concepts and the situational context of the teacher-researcher in order to understand a phenomenon that is closely related to their work. Therefore, this paper is focused on what we consider may be the first instance of this type of research, namely: hermeneutic reduction through auto-ethnography by the teacher-researcher.